2014
DOI: 10.1666/13083
|View full text |Cite
|
Sign up to set email alerts
|

Identification of chitin in 200-million-year-old gastropod egg capsules

Abstract: Chitin occurs in a variety of invertebrates, especially in arthropod cuticles, but is rarely reported in the fossil record. Although it has been detected in fossils as old as Middle Cambrian and Silurian, the majority of records come from much younger, Cenozoic deposits. In this paper, we report the preservation of chitin in Early Jurassic neritimorph gastropod egg capsules deposited in bivalve shells from prodelta-deltafront and nearshore paleoenvironments of the Holy Cross Mountains, Poland. We used a number… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 65 publications
(100 reference statements)
2
25
0
Order By: Relevance
“…As a preliminary procedure for identifying the intactness of chitin structures in these composites we used a specific chitin stain Calcofluor White (CFW), the fluorescent brightener [26,27,[39][40][41][42][43][44][45][46]. CFW binds to the glucan chains and linear β-(1,4)-glucosidically linked units of N-acetyl-D-glucosamine.…”
Section: Resultsmentioning
confidence: 99%
“…As a preliminary procedure for identifying the intactness of chitin structures in these composites we used a specific chitin stain Calcofluor White (CFW), the fluorescent brightener [26,27,[39][40][41][42][43][44][45][46]. CFW binds to the glucan chains and linear β-(1,4)-glucosidically linked units of N-acetyl-D-glucosamine.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, Ehrlich and co-workers reported that fragments of chitin fibers survived in the 505 million year old (Middle Cambrian) Burgess Shale Vauxia gracilenta sponge fossils [60]. The chitin found in these Vauxia sponge fossils is thus far the oldest known to show this exceptional chitin preservation, compared to previously reported chitin fossils [61,62].…”
Section: Historical Landmarks In the Discovery Of Chitinmentioning
confidence: 89%
“…2013). They are tough, leathery and, although composed of such organic compounds as conchiolin and chitin (Adegoke et al, 1969;Bandel 1982;Soliman 1987;Kano and Fukumori 2010;Fukumori et al, 2013;Wysokowski et al, 2014), they may additionally be strengthened by aragonitic or calcitic spherulites, as well as other different particles stored in the unique organ called the crystal sac (see Kano and Fukumori 2010;Fukumori et al, 2013). This feature gives the neritimorph egg capsules better fossilization potential than those produced by other gastropods.…”
Section: Preservationmentioning
confidence: 99%
“…Certainly, these egg capsules have not been reinforced by other particles as such were not detected. If the crystal sac and hence the calcium carbonatestrengthened egg capsules originated during the Late Cretaceous along with the divergence of the family Neritidae (see Fukumori et al, 2013), then the older neritimorphs could have produced "soft", unstrengthened egg capsules, composed of such organic compounds as chitin, which has been detected in the Early Jurassic egg capsules (Wysokowski et al, 2014).…”
Section: Preservationmentioning
confidence: 99%